Regulation of transcription of the adenovirus EII promoter by EIa gene products: absence of sequence specificity. - Kingston, R E (1984)
During adenovirus infection, the EII promoter is positively regulated by products of the EIa region. We have studied this regulation by fusing a DNA segment containing the adenovirus EII promoter to a dihydrofolate reductase cDNA segment. Expression of this hybrid gene is stimulated in trans when cell lines containing an integrated copy are either transfected with plasmids carrying the EIa region or infected with adenovirus. This suggests that EIa activity regulates transcription of the EII promoter in the absence of other viral proteins and that this stimulation can occur when the EII promoter is organized in cellular chromatin. Transcription from the EII promoter is initiated at two sites in cell lines lacking EIa activity. Introduction of the EIa region preferentially stimulated transcription from one of these two sites. A sensitive, stable cotransfection assay was used to test for specific EII sequences required for stimulation. EIa activity stimulates all mutant promoters; the most extensive deletion retained only 18 base pairs of sequences upstream of the initiation site. We suggest that regulation of a promoter by the EIa region does not depend on the presence of a set of specific sequences, but instead reflects a characteristic of promoters that have been exogenously introduced into cells. Insertion of the 72-base-pair repeat of simian-virus 40 in cis enhances transcription from the EII promoter. The stimulatory effects of EIa activity and of the simian virus 40 sequence are additive and appear to differ mechanistically.